2013
DOI: 10.1038/srep01813
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptor protein complexes-1 and 3 are involved at distinct stages of flavivirus life-cycle

Abstract: Intracellular protein trafficking pathways are hijacked by viruses at various stages of viral life-cycle. Heterotetrameric adaptor protein complexes (APs) mediate vesicular trafficking at distinct intracellular sites and are essential for maintaining the organellar homeostasis. In the present study, we studied the effect of AP-1 and AP-3 deficiency on flavivirus infection in cells functionally lacking these proteins. We show that AP-1 and AP-3 participate in flavivirus life-cycle at distinct stages. AP-3-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 29 publications
(36 reference statements)
2
37
0
Order By: Relevance
“…Other groups have implicated APs in the life cycle of multiple unrelated viruses (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and we reported roles for AP2 in HCV entry and assembly (22,23). Our work demonstrated that through AP2 phosphorylation, AAK1 and GAK regulate these temporally distinct steps of the HCV life cycle, thereby, for the first time, uncovering their role as "master regulators" of a viral infection (22,23).…”
Section: Resultssupporting
confidence: 54%
“…Other groups have implicated APs in the life cycle of multiple unrelated viruses (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and we reported roles for AP2 in HCV entry and assembly (22,23). Our work demonstrated that through AP2 phosphorylation, AAK1 and GAK regulate these temporally distinct steps of the HCV life cycle, thereby, for the first time, uncovering their role as "master regulators" of a viral infection (22,23).…”
Section: Resultssupporting
confidence: 54%
“…To achieve this, and to explore the possibility of CD2v contribution to Golgi and viral factory reorganization, we further characterized cellular markers of the TGN, potential candidates for interaction with the viral protein. One of the major players in Golgi organization is the AP-1 protein complex, which is involved in vesicle traffic between TGN and endosomes and is subverted by several viruses in order to modulate the infection [ 22 , 25 , 27 , 28 , 30 , 43 ]. Importantly, immune fluorescence assays showed that CD2v colocalized with AP-1 during ASFV-E70 infection in COS cells ( Fig 2A ) thus reinforcing a putative role for CD2v in Golgi reorganization during ASFV infection and in agreement with previous work showing ectopic CD2v in Golgi compartments [ 12 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…AP-1 has been shown to interact with several viral proteins including HIV-Nef and BPV-E6 [ 22 , 28 ]. The interaction between viral proteins and AP-1 has been proposed as a mechanism to subvert host cellular trafficking to ensure and optimize viral morphogenesis and viral egree while allowing immune evasion of the infected cell [ 25 , 27 , 28 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caco-2, A549, Huh-7, BHK-21, C6/36, HEp-2, PS, and MA104 cells were cultured as described previously (15)(16)(17). Virus strains used in the study and infection procedures has been described before (15)(16)(17). DENV-2 New Guinea C strain was a kind gift from Dr. Navin Khanna.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Most of the experiments have been performed in both the cell lines and we have obtained similar results. Plaque assay for DENV, JEV, and RV was set up in BHK-21, PS, and MA 104 cells respectively as described previously (15)(16)(17).…”
Section: Cells and Virusesmentioning
confidence: 99%